Performance comparison of 12s-14p inner and outer rotor field excitation flux switching motor - Syed Othman, Syed Muhammad Naufal (2014)

(untitled)
Hybrid excitation flux switching machines (HEFSMs) have a several advantages such as robust rotor structure, high torque and power capabilities, and high efficiency suitable for light load and heavy industry applications. However, the general structure of HEFSMs employed with three main flux sources namely permanent magnet (PM), field excitation coil (FEC) and armature coil located on the stator body causes high manufacturing cost. Therefore, a new non-PM field excitation flux switching machine (FEFSM) consists of rugged rotor structure suitable for highspeed operation with capability to keep similar torque and power density of HEFSM is proposed and examined. In this paper, performances of both outer and inner rotor 12S-14P FEFSMs are analyzed and compared. As conclusion, the inner-rotor topology provides much higher torque and power when compared with outer rotor configuration